Pemaknaan Khalayak Terhadap Lirik Lagu Kami Belum Tentu oleh Grup Musik .Feast - Duhita Anindyaguna, Karindra; Pudjo Santosa, Hedi (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2021)
A song titled â€œKami Belum Tentuâ€ portrays a gap of human rights in Indonesia. This research aimed to find out audience interpretation about marginalization in human rights and social criticism that is portrayed on the lyrics of â€œKami Belum Tentuâ€. This researched used Charles Osgoodâ€™s Osgood on Meaning message interpretation theory. Descriptive analysis is used to know the result of what people think after they read and heard the lyrics. The finding result shows that audience interpret the message differently because of the different experience as well as environment. The audience who came from Aksi Kamisan itself, the one who has â€˜wakil rakyatâ€™ as her family, and the fans of the group music itself. Which accepting the critics for the government as contained in the lyrics and agree that it is as nowadays reality. This research shows that audience are part of the community who are part of big heterogeneous mass community. As the part of community, audience are active where they are impervious of media influence. This research is open to be studied for future research with different methods as well as point of view